A Research Paper on the Influence of Blast Weakening on the Vibrations of Ground Buildings in a Shallow-Buried Extra-Thick Coal Seam - Gang Liu; Zijian Liu; Yingcheng Luan; Guohao Nie; Wangping Qian (Applied Sciences)
To learn more about the problem of blast weakening in shallow-buried and extra-thick coal seams, Panjin coal mine was used to provide the engineering background for this study. The influence of blast weakening technology on the vibration of ground buildings was investigated. Based on monitoring the vibration data from the final 400 m of the working face, we established the Sadovsky formula for this coal mine through regression. The maximum safe charge of one blast at different distances was obtained. A numerical model was established and compared with field monitoring data to verify its accuracy. This numerical model was used to analyze the influence of blast weakening vibrations on ground buildings during the final mining stage. Finally, the maximum safe charge for one blast at advancing distances from the working face was derived based on numerical calculation results. It was compared with the maximum safe charge obtained from field measurements. The results show that both exhibit significant consistency, and the maximum safe charge of one blast decreases as the working face advances. In addition, the peak vibration velocity at each monitoring point does not exceed 0.2 cm/s for the remaining 400 m of the measured working face, which is lower than the allowable safety value for blasting vibrations. In the numerical simulation of the final mining stage at 200 m, the ground vibration velocity is largest for the district office, second-largest for the chimney, and smallest for the science and technology building. The maximum vibration velocity and effective stress in the three directions of the three buildings are within the allowable range, indicating that the buildings remained in a safe state.